(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Mining of coal basically deals with the excavation of coal in a well-organized manner considering the People Security as well as safety. Mismanagement of the over burden leads to instability of slope and may cause a Greater loss of lives. The present paper mainly inspects the permanence of dump of a coal mine at Rajrappa Coal Mine, Ramgarh district, Jharkhand, by Analyzing various Geotechnical aspects of dumps and mineralogy of the slope. In 2016, a disaster due to dump failure in Rajmahal coalfield of Eastern Coalfield Limited, killed 23 workers. Even though all such accidents are being analyzed and recommendations made in each case, similar accidents are not prevented. Failure of the dump mainly occurs due to the pore water pressure. In order to satisfy the minimum factor of safety usingfellenious method, finally, an economical, sustainable, overall slope angle and height has been recommended so that maximum over burden can be dumped in a smaller area.